POPULATION DISTRIBUTION OF FRUIT FLIES PEST BACTROCERA SP. ON PAPAYA PLANTS IN SEVERAL LOCATIONS IN JEMBER DISTRICT - Gressia, Gene; Hasjim, Syaifuddin (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2023)
Papaya (Carica papaya L.) is a fruit with high economic value. Papaya production in Jember District in 2020 has decreased drastically to 55.8%. Production figures decreased from 215 thousand tons in 2019 to 95.1 thousand tons in 2020. The decline in production can be influenced by various factors, one of which is the lack of superior varieties cultivated and the development of pests and diseases. Fruit flies Bactrocera sp. are one of the pests that attack papaya plants and can cause fruit production failure in large quantities. Population distribution of fruit fly Bactrocera sp. on papaya plants needs to be investigated to determine its relationship with the intensity of attack by fruit fly pests Bactrocera sp. on papaya plants. This research was conducted on papaya plants in several locations in the Jember District. Sampling of fruit flies was carried out by setting traps using the Diagonal Sampling Technique by taking 5 sample points on each plot so that the sample points totaled 15 points. Data samples for calculating attack intensity were carried out by observing papaya fruit on 4 trees around the trap installation. So observations regarding the intensity of attacks were carried out on 60 papaya trees. The results showed that the distribution of fruit fly pest populations had a morbidity index value (Id < 1), meaning that fruit fly pests on papaya plantations had a regular distribution pattern. The intensity of attack by fruit flies on papaya plants is categorized as low attack intensity of 0% to 11.11%.